Klimaprobleme am Roten Meer - Flohn, Hermann (ERDKUNDE, 1965)
In the southern Red Sea area a unique combination occurs of winter rains at the bottom of the rift valley, of summer rains in the highlands and of rains during the whole year in the deeply dissected escarpment zone. This pattern is interpreted as a combined effect of a regional convergence between the channeled winds within the rift valley, local diurnal air circulations and various synoptic processes.